An Anopheles aquasalis GATA factor Serpent is required for immunity against Plasmodium and bacteria - Bahia, Ana C.; Kubota, Marina S.; Souza-Neto, Jayme A. [UNESP]; Koerich, Leonardo B.; Barletta, Ana Beatriz; Araújo, Helena R. C.; Gonçalves, Caroline M.; Ríos-Velásquez, Cláudia M.; Pimenta, Paulo F. P.; Traub-Csekö, Yara M. (Public Library of Science (PLoS), 2018)
Innate immunity is an ancient and conserved defense system that provides an early effective response against invaders. Many immune genes of Anopheles mosquitoes have been implicated in defense against a variety of pathogens, including plasmodia. Nevertheless, only recent work identified some immune genes of Anopheles aquasalis mosquitoes upon P. vivax infection. Among these was a GATA transcription factor gene, which is described here. This is an ortholog of GATA factor Serpent genes described in Drosophila melanogaster and Anopheles gambiae. Gene expression analyses showed an increase of GATA-Serpent mRNA in P. vivax-infected A. aquasalis and functional RNAi experiments identified this transcription factor as an important immune gene of A. aquasalis against both bacteria and P. vivax. Besides, we were able to identify an effect of GATA-Serpent knockdown on A. aquasalis hemocyte proliferation and differentiation. These findings expand our understanding of the poorly studied A. aquasalis-P. vivax interactions and uncover GATA-Serpent as a key player of the mosquito innate immune response.